Strategi Kerja Sama TNI–SAF dalam Integrasi UAV untuk Operasi Militer Selain Perang - Jeffrey Ng; Yermia Hendarwoto; Jimmy Veni Tokio (CV. ITTC INDONESIA, 2025)
This study analyzes the potential for bilateral military cooperation between the Indonesian National Armed Forces (TNI) and the Singapore Armed Forces (SAF) in utilizing Unmanned Aerial Vehicles (UAVs) for Military Operations Other Than War (MOOTW). Southeast Asia, particularly Indonesia and Singapore, faces unique vulnerabilities to natural disasters, maritime emergencies, and cyber counter-terrorism threats, requiring proactive military responses. Logistic support is crucial in military operations, focusing on supply chain management, sustainability, procurement, and crisis response. Military logistics modernization is considered central to future military actions. This research aims to formulate a practical framework encompassing joint UAV training, information-sharing mechanisms, standard operating procedures (SOPs), and airspace coordination arrangements. Despite institutional and technological challenges, this UAV cooperation can be built upon institutional trust and has the potential to positively influence not only bilateral relations but also serve as a model for multilateral collaboration in ASEAN. This framework is also expected to serve as a foundation for future multilateral UAV collaboration in ASEAN, while deepening bilateral ties between Indonesia and Singapore.